Sequential Push-Pull Pumping Mechanism for Washing and Evacuation of an Immunoassay Reaction Chamber on a Microfluidic CD Platform - Thio, Tzer Hwai Gilbert; Ibrahim, Fatimah; Al-Faqheri, Wisam; Soin, Norhayati; Bador, Maria Kahar; Madou, Marc (2015)
A centrifugal compact disc (CD) microfluidic platform with reservoirs, micro-channels, and valves can be employed for implementing a complete immunoassay. Detection or biosensor chambers are either coated for immuno-interaction or a biosensor chip is inserted in them. On microfluidic CDs featuring such multi-step chemical/biological processes, the biosensor chamber must be repeatedly filled with fluids such as enzymes solutions, buffers, and washing solutions. After each filling step, the biosensor chamber needs to be evacuated by a passive siphoning process to prepare it for the next step in the assay. However, rotational speed dependency and limited space on a CD are two big obstacles to performing such repetitive filling and siphoning steps. In this work, a unique thermo-pneumatic (TP) Push-Pull pumping method is employed to provide a superior alternative biosensor chamber filling and evacuation technique. The proposed technique is demonstrated on two CD designs. The first design features a simple two-step microfluidic process to demonstrate the evacuation technique, while the second design shows the filling and evacuation technique with an example sequence for an actual immunoassay. In addition, the performance of the filling and evacuation technique as a washing step is also evaluated quantitatively and compared to the conventional manual bench top washing method. The two designs and the performance evaluation demonstrate that the technique is simple to implement, reliable, easy to control, and allows for repeated push-pulls and thus filling and emptying of the biosensor chamber. Furthermore, by addressing the issue of rotational speed dependency and limited space concerns in implementing repetitive filling and evacuation steps, this newly introduced technique increases the flexibility of the microfluidic CD platform to perform multi-step biological and chemical processes.